A constituição e sua defesa: Ministério Público como defensor da constituição - Corrêa, Marcos José Gomes (2006)
The present dissertation is intended to examine, from its beginnings, the concept of Constitution and to demonstrate its double significance, political and legal, as well as the means used to guarantee the prevalence of the Constitution in European and North American traditions. The vicissitudes of the defence of the Constitution in Brazil, the broad outlines of organisation and operation of the Judiciary - which, starting from the establishment of the Republican regime in Brazil, had a duty to analyse legislation by contrasting it with the Constitution, thereby confirming its validity - and the role of the Brazilian Public Prosecution Service as an active defender of the Constitution, are also examined. The dissertation confronts the issue of the judicialisation of politics and hopes to demonstrate that the increase in social, cultural and economical rights, in peripheral countries such as Brazil, compels the legal system to enter into contact with conflicts generated in other social systems (economy, health, education, religion, sport etc), the Public Prosecution Service being an important channel - at the same time as introducing discussions about social, cultural and economical rights - for the preservation of the judicial system code (lawful/unlawful) and its self-generating, or "autopoiético", character to keep the centre of the judicial system free of spurious interference from the other social systems